Misi Dakwah dan Transformasi Sosial: Studi kasus Di Bayan, Lombok Barat. - Erni Budiwanti (LIPI Press, 1998)
This writing is based on a fieldwork research conducted in 1993 in the village of Bayan, Bayan sub-district of West Lombok regency. In general it discusses on the proliferation of Islamic teaching in Lombok. It is unique that the process of Islamisation in Lombok has created two segments of the Sasak society into the Wetu Telu and the Waktu Lima. The Wetu Telu are the Sasak who, although acknowledging themselves to be Muslims, still believe strongly in the ancestral animistic deities as well as anthropomorphized inanimate objects. In other words, they are pantheists. The Waktu Lima, on the other hand, are those Sasak Muslims who follow more strictly to the standardized Islamic rules (syari’ah) as prescribed by the Qur’an and the hadith. This reality had instigated some leading figures, the Tuan Guru, to Import pure Islamic teachings. The Tuan Guru’s religious activity, called misi dakwah has intensively entered into various Wetu Telu areas to purify Islam from what seems to them animism and other diverse local cultural practices which are pre-Islamic. This activity has been successful in converting many Wetu Telu villagers all over Lombok to be stricter Islamic proctitioners or the Waktu Lima. If the earlier dakwah led by Tuan Guru was characterized by the use of miracles, the more recent Islamic mission, especially since in the beginning of 20th century, is marked by the cooperation of Tuan Guru with local government authorities, and other international organizations. Such cooperation has increased the quality of the dakwah. Dakwah not only seeks to improve the religious affiliation of the Wetu Telu, but at the some time is also intended to improve the living standard of the people in all aspect of life.